OMORGUS (OMORGUS) SUBEROSUS (FABRICIUS) (COLEOPTERA: TROGIDAE) EM ESTERCO DE GALINHAS POEDEIRAS DE SÃO JOÃO DA BOA VISTA, SP, BRASIL - Lopes, W.d.z. [UNESP]; Costa, F.h. Da; Lopes, W.c.z.; Balieiro, J.c. De C.; Soares, V.e. [UNESP]; Prado, Â.p. Do (Instituto Biológico, 2022)
The family Trogidae (Coleoptera) is cosmopolitan and its species are mainly necrophagous. Studies on Omorgus (Omorgus) suberosus (Fabricius, 1775) on excrements in poultry houses are needed due to the scarcity of published information on the species in this kind of environment. A survey for this trogid was carried out in a poultry house in São João da Boa Vista, SP, Brazil, from January 2001 to December 2002 using soil and water flotation traps and Berlese-Tullgren funnel. A total of 2,322 specimens of O. suberosus were collected, being 99.17% by soil trap, 0.51% by Berlese-Tullgren funnel and only 0.30% (7 specimens) by water flotation trap. A significant increase in the capture (P < 0.05) of O. suberosus was registered in the summer of 2001/2002, and the soil trap proved to be the most appropriate method (P < 0.05) for capture of this species.

A família Trogidae (Coleoptera) é cosmopolita e suas espécies têm hábitos principalmente necrófagos. Estudos com Omorgus (Omorgus) suberosus (Fabricius, 1775), em fezes de granja aviária devem ser realizados, uma vez que poucas informações sobre esta espécie, neste tipo de ambiente, estão disponíveis na literatura. Foi realizado um levantamento deste trogídeo em granja de aves poedeiras situada em São João da Boa Vista, SP, Brasil, entre janeiro de 2001 a dezembro de 2002, utilizando-se, para captura, armadilhas de solo, funil de Berlese–Tullgren e flutuação em água. Dos 2.322 espécimes de O. suberosus coletados, armadilhas de solo somaram 99,17% do total, 0,51% pelo funil de Berlese–Tullgren e apenas 0,30% (sete espécimes) foram capturados pela flutuação em água. Aumento significativo (P < 0,05) na captura de O. suberosus foi registrado no verão de 2001 / 2002, além do que a armadilha de solo mostrou ser o método mais apropriado (P < 0,05) para capturar esta espécie.
OMORGUS (OMORGUS) SUBEROSUS (FABRICIUS) (COLEOPTERA: TROGIDAE) IN POULTRY MANURE IN SÃO JOÃO DA BOA VISTA, SP, BRAZIL
Keywords: Poultry house; Insecta; Omorgus suberosus; Trogidae; Granja avícola; Insecta; Omorgus suberosus; Trogidae